Aplikasi ayat-ayat bisnis dalam al-Qur’an pada pesantren enterpreneur: studi kasus di Pondok Pesantren Sidogiri Pasuruan - Moh. Toriquddin (Ijtihad : Jurnal Wacana Hukum Islam dan Kemanusiaan, 2015)
This research discusses the application of Quran verses of business in Sidogiri boarding school, Pasuruan.It is aimed at explaining how verses of business in the Holy Quran are applied in the business ofSidogiri boarding school, Pasuruan. Qualitative research is applied. Data are analyzed through thematicinterpretation. The study shows that the application of verses of business in the Quran is a form ofworship. Professionalism and ethic of business in BMT UGT Sidogiri has already been well practiced asa form of worship which employs legal contract in Islamic law; application of principle of honesty(shiddiq), communicativeness (tablig), trustworthiness (amanah), and professional (fatanah) in runningbusiness as the manifestation of worship in Allah. Professionalism in business can be known from theuse of justice principle; the absence of additional money from customer, the guarantee of keepingcustomer’s privacy, and the modern system of money management which uses e-banking system. Ethicof business is such particular soft rejection towards customers and good service.